2017
DOI: 10.1088/1361-6528/aa5ec1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical characterization of GaAs nano-crystals selectively grown on Si nano-tips by MOVPE

Abstract: We present the nanoheteroepitaxial growth of gallium arsenide (GaAs) on nano-patterned silicon (Si) (001) substrates fabricated using a CMOS technology compatible process. The selective growth of GaAs nano-crystals (NCs) was achieved at 570 °C by MOVPE. A detailed structure and defect characterization study of the grown nano-heterostructures was performed using scanning transmission electron microscopy, x-ray diffraction, micro-Raman, and micro-photoluminescence (μ-PL) spectroscopy. The results show single-cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Further fabrication details can be found in refs. [43][44][45] In the following, we name as "sample A" the InP-NCs/Si-tips and as "sample B" the Gr/InP-NCs/Si-tips. Scanning electron microscopy (SEM) tilted- Electrical measurements were performed inside a Zeiss LEO 1430 SEM chamber in high vacuum (< 10 -6 Torr) and at room temperature.…”
mentioning
confidence: 99%
“…Further fabrication details can be found in refs. [43][44][45] In the following, we name as "sample A" the InP-NCs/Si-tips and as "sample B" the Gr/InP-NCs/Si-tips. Scanning electron microscopy (SEM) tilted- Electrical measurements were performed inside a Zeiss LEO 1430 SEM chamber in high vacuum (< 10 -6 Torr) and at room temperature.…”
mentioning
confidence: 99%
“…The main steps for the fabrication of the substrates include deposition of SiO 2 and Si 3 N 4 , lithography, dry and wet etching, chemical mechanical planarization, and final wet cleaning. More details are given by Skibitzki et al (2017) and Niu et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The epitaxial growth of GaAs with the zincblende/sphalerite ZnS-type structure [space group F " 4 43m, Pearson symbol cF8, lattice parameter a = 0.5654 nm, with Ga at the Wyckoff position (4a) 0, 0, 0 and As at (4c) 1 4 , 1 4 , 1 4 (Villars & Cenzual, 2016/17)] on Si with the diamond C-type structure [Fd " 3 3m, cF8, a = 0.5430 nm, with two face-centred cubic (f.c.c.) sublattices shifted by 1 4 , 1 4 , 1 4 along the body diagonal (Villars & Cenzual, 2016/17)] is, however, challenging because of the significant lattice mismatch of 4.1% and the difference in thermal expansion coefficients (Bolkhovityanov & Pchelyakov, 2008;Prieto, Kozak, Skibitzki, Rossell, Zaumseil et al, 2017;Skibitzki et al, 2017). This leads to the formation of various crystal imperfections (dislocations, stacking faults, twins etc.)…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, several technical difficulties to overcome, such as dislocations induced by the lattice mismatch, the cracks due to the differences in the thermal expansion coefficient, and the anti-phase boundary resulting from the growth of the polar III–V compounds on nonpolar Si. Many attempts have been made to solve these problems, and it has been found that selective area growth (SAG) is one of the effective ways of suppressing the propagation of dislocations and cracks as well as lowering the density of the anti-phase boundary 47 . The III–V compounds grown via SAG is in the form of quantum dots 6,816 or nanowires 10,11,17 .…”
Section: Introductionmentioning
confidence: 99%